Morphological Study of Oropharyngeal Cavity and Histochemical Characteristic of Palatine Salivary Glands in Domesticated Goose (Anser anser domesticus) - Hadia Zorab (Basrah Journal of Veterinary Research)
AbstractThis research planned to investigate the morphological structures of the oropharynx cavity and microscopic features of palatine salivary glands in domesticated goose. Ten heads of adult healthy geese collected from slaughterhouse. Five heads were prepared for macroscopic examination and five heads were processed for histochemical investigation of the palatine salivary glands. Anatomically, the oropharynx cavity was divided into roof and floor. The oropharyngeal roof composed of the rostral region (lamellae part) and the caudal region (papillae part). Median palatine ridge divided lamellar part into two equal sides. Each side had three longitudinal rows of palatine round tubercle. The oropharyngeal floor subdivided into rostral part occupying by the tongue and caudal part including the laryngeal mound. Horny bristle lamellae existed on the lateral margins of the beak. Three clefts were observed including choanae, infundibular cleft and glottis. The tongue was flat elongated and rostrally carried the lingual nail. The microscopic findings showed that the palatine salivary glands were mucus secreting and simple branched tubular glands. A mucus cell was tall columnar with basally located nucleus. Also, the mucus cell secreted neutral and acid mucosubstances but proteins and glycogens were absent. The palatine glands contained numerous lymphatic nodules which protected the oropharyngeal mucosa from invasion of microorganisms. The characteristic features of the oropharynx and secretions of the palatine glands showed their adaptation based on the type of food and feeding behavior in domesticated goose.